Prophetic Role Modeling and Character Education in the Modern Era: A Systematic Literature Review - Sanudin Ranam; Ibnu Fiqhan Muslim; Priyono; Muhammad Arifin (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2025)
In the modern era, one of the major challenges in character education lies in effectively instilling moral and ethical values amid rapid social change. The decline in moral standards within society is frequently associated with the suboptimal implementation of moral education across families, formal educational institutions, and broader social environments. At the same time, the effectiveness of value-based education within formal schooling continues to be widely debated, particularly regarding its relevance in contemporary contexts. This study aims to examine the relevance and significance of the educational exemplarity of the Prophet Muhammad (peace be upon him) as a foundational framework for character education in the modern era. Employing a literature review approach, this study analyzes classical and contemporary scholarly works related to prophetic education, moral development, and character formation. The findings indicate that the Prophet Muhammad’s educational model emphasizes universal values such as moral integrity, responsibility, independence, cooperation, and social harmony. The family is identified as a crucial foundational unit in character formation, especially during early childhood, which represents a critical phase for moral development. Furthermore, prophetic teachings highlight the importance of collaboration, mutual assistance, and community-based engagement as key elements in fostering social cohesion and collective well-being. This study concludes that the educational exemplarity of the Prophet Muhammad remains highly relevant for addressing contemporary challenges in character education and offers a comprehensive, value-based framework adaptable to modern educational contexts.